2007
DOI: 10.1021/om070087y
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Desulfurization of Dibenzothiophene and Its Hindered Analogues with Nickel and Platinum Compounds

Abstract: II oxidation states containing mono-and diphosphines ligands, in conjunction with alkyl Grignard reagents, promoted the desulfurization of dibenzothiophene (DBT), 4-methyldibenzothiophene (4-MeDBT), and 4,6-dimethyldibenzothiophene (4,6-Me 2 DBT), to produce the corresponding substituted and unsubstituted biphenyls. It was also observed that the use of polar solvents such as THF yielded thiols, while the use of nonpolar solvents allowed the complete desulfurization of these substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Metal-mediated activation of strong bonds, such as C−C, C−H, C−O, and C−X (X = halogen), is a vital research area related to the catalytic transformation of organic molecules. , Carbon−sulfur bonds are also activated on metal centers to provide useful reaction pathways for novel sulfur-containing compounds. , The C−S bond cleavage of thiophenes is an industrially important process in catalytic hydrodesulfurization (HDS) that removes sulfur from organosulfur compounds in petroleum feedstocks . The research on HDS of thiophenes gave various metallacyclic compounds having thiolato-S coordination in addition to valuable insights about the C−S bond cleavage. The reactions of dibenzothiophenes (DBT) with organometallic compounds are of particular interest because dibenzothiophenes are especially resistant to desulfurization, which causes serious problems for further HDS. , The rich sulfur−metal chemistry originating from HDS would provide new ways to produce S-containing functional materials. In this context, we started research on the metallacyclic compounds with a pincer frame derived from dibenzothiophenes via the C−S cleavage reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-mediated activation of strong bonds, such as C−C, C−H, C−O, and C−X (X = halogen), is a vital research area related to the catalytic transformation of organic molecules. , Carbon−sulfur bonds are also activated on metal centers to provide useful reaction pathways for novel sulfur-containing compounds. , The C−S bond cleavage of thiophenes is an industrially important process in catalytic hydrodesulfurization (HDS) that removes sulfur from organosulfur compounds in petroleum feedstocks . The research on HDS of thiophenes gave various metallacyclic compounds having thiolato-S coordination in addition to valuable insights about the C−S bond cleavage. The reactions of dibenzothiophenes (DBT) with organometallic compounds are of particular interest because dibenzothiophenes are especially resistant to desulfurization, which causes serious problems for further HDS. , The rich sulfur−metal chemistry originating from HDS would provide new ways to produce S-containing functional materials. In this context, we started research on the metallacyclic compounds with a pincer frame derived from dibenzothiophenes via the C−S cleavage reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[53] From the intermediates proposed in the two cycles, the thia-nickela-cycle A and others were recently prepared independently, isolated and characterized. The latter is explained on the basis of the large steric hindrance that the substrate, the Grignard reagent and the ancillary ligand oppose to each other.…”
Section: ) Use Of Low-valent Nickel Compounds In Desulfurization Reamentioning
confidence: 99%
“…The isolation and characterization of the latter sulfide was ensured during the study, confirmed to be formed in every experiment. A comprehensive mechanistic proposal that illustrates the C–C cross coupling reaction along with and the β‐elimination of hydrogen that leads to the formation of biphenyl, using low‐valent nickel is included in Scheme 53…”
Section: ) Use Of Low‐valent Nickel Compounds In Desulfurization Reamentioning
confidence: 99%
“…A ring-opening mechanistic pathway via a sulfinametallacycle of the type [(dippe)­Ni­(κ 2 - C,S -DBTO 2 )] was suggested as a key intermediate in the mechanistic proposal over a pathway via the reduction of the corresponding sulfone to dibenzothiophene; the latter was initially ruled out considering the high oxidesulfurization yields that would not be expected if DBTs could be generated from DBTsO 2 . However, the corresponding nickel intermediates could not be isolated or detected in solution (Scheme ).…”
Section: Introductionmentioning
confidence: 99%